Shaving without hurting the hegemonic masculinity: the introduction of the safety razor in Brazil (Revista Angelus Novus, 2023)
For centuries, men have incorporated the care of their beards into their daily routines, either by maintaining a specific shape or by removing it entirely. This grooming practice, which involves the use of creams, lotions, mirrors, and a focus on appearance, could be considered a self-care. However, the act of shaving is rarely seen as a beauty routine. This article aims to examine how Gillette razor advertisements in Brazil during the first half of the 20th century promoted the product without linking it to beauty, which was traditionally considered a feminine domain.